2015
DOI: 10.1016/j.pbb.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and cognitive effects of tyrosine intake in healthy human adults

Abstract: The amino acid tyrosine is the precursor to the catecholamine neurotransmitters dopamine and norepinephrine. Increasing tyrosine uptake may positively influence catecholamine-related psychological functioning. We conducted a systematic review to examine the effects of tyrosine on behavior and cognition. Fifteen studies were reviewed. All studies except one involved tyrosine loading during a single test session. In most behavioral studies, there were no significant effects of tyrosine on exercise performance. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Third, Hase, Gorrie-Stone and Freeman (2019) evaluate challenge and threat states as candidate mechanisms to explain the effects of a nutritional supplementtyrosineon performance. In accord with previous supplementation research (e.g., Hase, Jung & Rot, 2015), tyrosine ingestion benefited motor performance. While tyrosine did not directly influence cardiovascular reactivity, regression analyses revealed that more threat-like cardiovascular responses were associated with better performance during the tyrosine supplementation.…”
Section: Introduction To the Special Issuesupporting
confidence: 89%
“…Third, Hase, Gorrie-Stone and Freeman (2019) evaluate challenge and threat states as candidate mechanisms to explain the effects of a nutritional supplementtyrosineon performance. In accord with previous supplementation research (e.g., Hase, Jung & Rot, 2015), tyrosine ingestion benefited motor performance. While tyrosine did not directly influence cardiovascular reactivity, regression analyses revealed that more threat-like cardiovascular responses were associated with better performance during the tyrosine supplementation.…”
Section: Introduction To the Special Issuesupporting
confidence: 89%
“…Recent research was able to show evidence for positive effects of dietary tyrosine intake on cognitive function in healthy humans (Kühn et al, 2017), which were similar to the ones observed after single high dose intake of tyrosine (Hase et al, 2015, Jongkees et al, 2015.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, vanylmandellic acid—an end-product of the tyrosine pathway—was found to be increased in the CSF of AD patients [37], suggesting disturbances of the tyrosine pathway. Dopamine has been associated with cognitive control [38], and oral supplementation of tyrosine has been shown to improve working memory and information processing during demanding situations in healthy human adults [39]. Experimental studies are needed to establish if the alterations in peripheral tyrosine metabolism we found in our study also affect the function of dopamine and tyrosine in the central nervous system of AD patients.…”
Section: Discussionmentioning
confidence: 79%